2020
DOI: 10.7759/cureus.11784
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Comparability and Interchangeability Between Daytime Ambulatory Blood Pressure Monitoring and 24-Hour Ambulatory Blood Pressure Monitoring in Detecting Masked Hypertension

Abstract: Background The primary aim of this study was to evaluate the level of diagnostic overlap between daytime ambulatory blood pressure (BP) monitoring (DT-ABPM) and 24-hour ambulatory BP monitoring (24-h ABPM) in detecting masked hypertension (MH). Methods This is a prospective study that was performed in a sample of 196 soldiers aged between 21 and 50 years (without a history of hypertension) undergoing ABPM testing. The diagnosis of MH based on DT-ABPM defined as (office blood pressure (OBP) <140/90 and DT-ABPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to the World Health Organization (WHO), hypertension which is considered as a significant risk factor of cardiovascular diseases (CVDs) accounting for about 32 percent for worldwide deaths [2]. Regular blood pressure monitoring is therefore crucial for the entire people, but it is especially crucial for those who already have hypertension or other disorders that are associated because they are more susceptible to elevated blood pressure [3]. It is reported that there are various ways to estimate blood pressure variations either using the Photoplethysmogram signal (PPG) then applying machine learning algorithms to detect the variations of blood pressure or by measuring the time difference between the peaks of electrocardiogram (ECG) and Photoplethysmogram (PPG) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), hypertension which is considered as a significant risk factor of cardiovascular diseases (CVDs) accounting for about 32 percent for worldwide deaths [2]. Regular blood pressure monitoring is therefore crucial for the entire people, but it is especially crucial for those who already have hypertension or other disorders that are associated because they are more susceptible to elevated blood pressure [3]. It is reported that there are various ways to estimate blood pressure variations either using the Photoplethysmogram signal (PPG) then applying machine learning algorithms to detect the variations of blood pressure or by measuring the time difference between the peaks of electrocardiogram (ECG) and Photoplethysmogram (PPG) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), elevated blood pressure is considered as a signi cant risk factor of cardiovascular diseases (CVDs) accounting for about 32 percent of worldwide mortality [2]. Regular out-of-o ce blood pressure monitoring is therefore crucial, especially for those who already have hypertension or other disorders that are associated with hypertension [3]. Continuous, wearable blood pressure devices are therefore essential for real-time evaluation of blood pressure and timely intervention [4].…”
Section: Introductionmentioning
confidence: 99%